A qualitative study of the continuing professional development activities of the Chinese private kindergarten teachers’ professional competence - Liu, Xiaojing; Li, Yulong (Journal of Education Culture and Society, 2021)
Aim. The number of kindergartens is swelling in China, and that of private kindergartens in particular. The quality of teaching in the latter is positively linked to the levels of teachers’ professional competence. Thus, to enhance the teaching quality in private kindergartens, strengthening teacher’s professional competence is one of the vital approaches. Teacher’s professional competence can be enhanced via effective CPD activities. Therefore, this study aims to explore the types and content of CPD activities for Chinese private kindergarten teachers. Methods. A qualitative approach was adopted in this research. 18 kindergarten teachers were selected as participants from three private kindergartens in Shenzhen. Data was collected by semi-structured interview from 18 teachers. Results and conclusion. The findings showed that the school-based CPD activities are valued by most private kindergarten teachers. Furthermore, this study found that CPD activities can help private kindergarten teachers to be more inclusive and positive in teaching. They enabled teachers to acquire knowledge and skills that are relevant to child care and development, teaching, as well as cooperation with colleagues and children’s parents. Practical application. The research findings presented herein have significant implications for the knowledge base of private kindergarten teachers’ CPD in China. It also has implications for the practice that is relevant to private kindergarten teachers, principals and policy makers.